2019
DOI: 10.1017/s2040174419000047
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean delivery, immune function and inflammation in early life among Ecuadorian infants and young children

Abstract: Caesarean delivery has been linked to a number of inflammatory conditions in childhood and adolescence. Yet the mechanisms underlying these associations and their generalizability across contexts with different postnatal feeding and pathogenic exposures remain unclear. This study tests the association between delivery type and three measures of immune function, inflammation, morbidity and leukocyte proportions, in Ecuadorian infants and children aged 6 months to 2 years. Data were collected from mother–child p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…In a recent study, Davoodi et al 42 observed a positive correlation between asthma and socioeconomic status. In two studies conducted in Ecuador by Jahnke et al, 15 the authors noted an increased rate of CS in Ecuadorian women with higher income and suggested that the mode of delivery may be associated with an altered inflammatory response to infection and changes in the proportion of cells involved in the allergic response 23 . Our study substantiates these conclusions since we were also able to delineate an increased occurrence of allergic diseases in higher social strata.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…In a recent study, Davoodi et al 42 observed a positive correlation between asthma and socioeconomic status. In two studies conducted in Ecuador by Jahnke et al, 15 the authors noted an increased rate of CS in Ecuadorian women with higher income and suggested that the mode of delivery may be associated with an altered inflammatory response to infection and changes in the proportion of cells involved in the allergic response 23 . Our study substantiates these conclusions since we were also able to delineate an increased occurrence of allergic diseases in higher social strata.…”
Section: Discussionsupporting
confidence: 87%
“…In two studies conducted in Ecuador by Jahnke et al, 15 the authors noted an increased rate of CS in Ecuadorian women with higher income and suggested that the mode of delivery may be associated with an altered inflammatory response to infection and changes in the proportion of cells involved in the allergic response. 23 Our study substantiates these conclusions since we were also able to delineate an increased occurrence of allergic diseases in higher social strata. Regarding sex, age, and mode of delivery, socioeconomic status appeared to be a significant predictor of asthma, physician-diagnosed rhinitis, the occurrence of rhinitis symptoms (such as itching of the nasal tract, nasal secretion, and blocked nose), and food allergies.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations